Collaborative Governance dalam Perlindungan Tenaga Kerja Wanita di Kabupaten Serang pada Tahun 2018 - Toriq Nauval; Ipah Ema Jumiati; Bayu Nurrohman (Epistemik: Indonesian Journal of Social and Political Science, 2022)
The implementation of collaborative governance in the protection of Women's labor in Serang regency in 2018 is one of the solutions in solving the problem of Women's labor in Serang regency. Serang Regency area ranked first in banten province with 696 people in 2018. Therefore, the concept of collaborative governance is very suitable to be carried out to cooperate in solving the problems of this woman's workforce. This study measured the success rate of De Seve's theory, collaborative governance theory. The basis of this theory is 8 measures of success, namely, network structure, commitment to goals, the existence of anxiety between actors in the network, the existence of certainty, access to power, sharing accountability for information sharing and access to resources. This study uses qualitative research methods. Data collection was carried out observations down directly to interview the Disnaker Serang Regency, BP3TKI and SBMI. The results of this study explain how this collaborative governance process has not run optimally. The absence of administratively formed networks and the absence of agreements between these three agencies have difficulty carrying out collaboration. So that researchers encourage related agencies to encourage the creation of agreements between agencies so that administratively and legally clear their positions so that they can carry out the collaboration of women's labor protection to the maximum.